Analysis Of Troponin T Examination Results In Acute Myocard Infark Patients In Santa Elisabeth Hospital Medan, 2022 - Paska Ramawati Situmorang; Fransiskanes Manurung; Rica Vera Br.Tarigan (Jurnal EduHealth, 2022)
Infarction Acute Myocardial (AMI) is damage to myocardial tissue due to severe ischemia that occurs suddenly. The incidence of heart disease undergoing inpatient and outpatient treatment in hospitals in Indonesia in 2019 was 239,548 people (WHO). IMA is included in the top 10 categories of non-communicable diseases that are the cause of death in hospitals throughout Indonesia, around 6.25%. Troponin T is a cardiac contractile regulatory protein molecule that can measure normal and abnormal levels to help diagnose AMI. The purpose of this study was to analyze troponin-T levels in AMI patients, and the average (percentage) results of troponin-t examinations in AMI patients at St.Elisabeth Hospital Medan 2022. This type of research is an observational descriptive designed. The sampling technique in this study is retrospective. The population are 240 people and the research sample are 93 people. The results of this study conduc on 93 patients show an average troponin T level of 13.07 ng/ml, SD 17.44949, most of the patients were 64 men (68.8%) and 29 women (31 ,2%) with the lowest age are 37 years and the highest are 79 years. The results show that 94.6% of AMI patients experienc an increase in troponin T levels. Patients with acute myocardial infarction when an infarction occurred, it will experience increased levels due to the release of the troponin T enzyme through membrane leakage due to necrosis, so it will show a peak value on examination.